Determination of metal ions in fuel ethanol after preconcentration on 5-amino-1,3,4-thiadiazole-2-thiol modified silica gel - Gomes, Luis A. de Melo [UNESP]; Padilha, Pedro de Magalhães [UNESP]; Moreira, José Celso [UNESP]; Dias Filho, Newton L. [UNESP]; Gushikem, Yoshitaka (FapUNIFESP (SciELO), 1998)
This work describes the synthesis and characterization of 5-amino-1,3,4-thiadiazole-2-thiol modified silica gel (SiATT), and the results of a study of the adsorption and preconcentration (in batch, and in flow using a column technique) of Cd(II), Co(II), Cu(II), Fe(III), Ni(II), Pb(II) and Zn(II) in ethanol medium. The adsorption capacities for each metal ion were (in mmol g -1): Cd(II) = 0.11, Co(II) = 0.10, Cu(II) = 0.20, Fe(III) = 0.20, Ni(II) = 0.16, Pb(II) = 0.08 and Zn(II) = 0.12. The results obtained in the flow experiments, showed a recovery of ca. 100% of the metal ions adsorbed in a column packed with 2 g of SiATT, using 5 mL of 2.0 mol L -1 HCl solution as eluent. The sorption-desorption of the metal ions made possible the development of a preconcentration method and quantification by Flame AAS of metal ions at trace level in fuel ethanol.
Keywords: 5-amino-1,3,4-thiadiazole-2-thiol modified silica gel; Fuel ethanol; Preconcentration